Promoting user-centricity in short-term ideation workshops. Issue 3 (2nd October 2018) - Heck, Johannes; Rittiner, Florian; Meboldt, Mirko; Steinert, Martin
Abstract: Participating in a short-term ideation workshop – based on design thinking principles – may increase the innovation capability of companies. We show how the persona methodology can be successfully applied to promote user-centricity in such ideation workshops. For this research, we observed 20 design teams of Swiss Small and Medium-sized Enterprises during 2.5-day standardized ideation workshops, and analyzed how they developed and used – in total 81 – personas as a design tool to inform their product and service development activities. We found that an iterative approach, which allows for frequent reality checks during the persona development process, in combination with diversely staffed design teams, who bring a broad range of expertise and experiences together, may compensate for the limited amount of time available for user research during short-term ideation workshops. Moreover, our study revealed two varying persona usage patterns, namely personas used as a reference point versus personas used as a starting point. These findings highlight personas as a valuable design tool to promote user-centricity during short-term ideation workshops in the early development phase of new products, services and business models.